PENGARUH GAYA HIDUP, KONTROL DIRI DAN STATUS SOSIAL TERHADAP PENGELOLAAN KEUANGAN PRIBADI PADA KARYAWAN UPT PUSKESMAS MOYO HULU - Aminah, Siti; Hartini (Jurnal Nusa Manajemen, 2024)
This research aims to determine the influence of lifestyle, self-control and social status on personal financial management among UPT Puskesmas Moyo Hulu employees. Financial management is very important for every individual to achieve a prosperous future and avoid various financial problems. This research uses quantitative methods with an associative approach. The datacollection method uses a questionnaire with a Likert scale. The population in this study was all employees of the Moyo Hulu Community Health Center with the sampling method using a saturated sampling technique and the sample used was 86 respondents. The method used is multiple linear regression analysis with data processing using the SPSS program. The research results show that the variables of lifestyle, self-control and social status partially have a positive and significant influence on the personal financial management of Moyo Hulu Community Health Center employees.